Исследование влияния ширины ветви плавкого элемента на защитные характеристики быстродействующих предохранителей - Фомин, Василий Иосифович (НТУ "ХПИ", 2005)
В статье проведен расчет сечения плавкого элемента для различной геометрии плавкого элемента, расчет основных защитных при отключении токов короткого замыкания и влияния на них ширины ветви плавкого элемента.

The paper presents calculations of conducting element cross-section for various conducting element geometries as well as calculations of the basic protective characteristics under short-circuit current interruption and influence of the conducting element branch width on them.
Research into influence of conducting element branches on protective performance of quick-break fuses
Keywords: электрические аппараты; плавкие предохранители; геометрия плавкого элемента; токи короткого замыкания; protective performance; quick-break fuse; conducting element